Conceptual Metaphors in A Collection of Cirebon Folklore by Made Casta and Masduki Sarpin - Afina Naufalia; Tajudin Nur; Sutiono Mahdi; Agus Suherman Suryadimulya (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
This research is motivated by themetaphorical language that often appears in literary works because literary works contain many connotative meanings, so they use majas. One of the literary works is folklore. In this study, researchers were interested in analyzing conceptual metaphors found in several folklore. The source of the research used is based on a collection of folklore entitled "Folklore from Cirebon" by Made Casta and Masduki Sarpin published in 1998. That way, the purpose of this study is to describe the types of metaphors, conceptual meanings, and image schemes in the cirebon folklore collection. This research uses descriptive qualitative methods. The data collection technique in this study is a reading and note-taking technique, namely by reading the book of the collection of folklore, then recorded and classified the type of metaphor obtained. The data analysis techniques used are analysis techniques according to Miles and Huberman (1992), namely: (1) data reduction (data reduction), (2) data presentation (data display), and (3) conclusion drawing. From the research, the results were obtained, namely from the 6 folklore analyzed, there were 14 data that contained metaphorical meanings. The metaphor is based on three types of metaphors, namely structural, orientational, and ontological. The results stated that this collection of folklore from Cirebon uses the most orientational metaphors with the image scheme that appears the most is the spatial image scheme. Both metaphors and image schemes are found in many folklore entitled The Origin of the Name Cirebon. This research is expected to be useful for literature learning in high school and for the advancement of conceptual metaphorical research.